Poland and Transatlantic Security – an Enduring Atlanticist? - Kerry Longhurst (Romanian Journal of European Affairs)
Throughout the 1990’s Poland pursued a security policy steered by Atlanticism and a close bond with the United States. Atlanticism shaped Warsaw’s choices on all key security issues during the past decade, but became particularly apparent after 9/11 when Poland lent its full support to the US-led war on terror. Whilst membership in the EU will affect the priorities and conduct of Polish security policy, it is argued here that the deep-seated nature of Atlanticism in Polish strategic culture , together with the broader implications of enlargement upon the EU’s foreign policy ambitions will ensure that Poland will remain a keen Atlanticist in the New Europe.